Analisis Kinerja Keuangan dengan Pendekatan FVA (Financial Value Added) - Siti Kholifah; Jawoto Nusantoro; Elmira Febri Darmayanti (Universitas Muhammadiyah Metro, 2026)
institutions listed on the Indonesia Stock Exchange based on liquidity, solvency, profitability, and Financial Value Added (FVA). This study uses purposive sampling with specific criteria, resulting in four Sharia banks selected as samples. The results show that the financial performance analysis of Sharia banks listed on the Indonesia Stock Exchange based on liquidity varies during the 2021–2024 period. Based on solvency, the financial performance of the four sampled Sharia banks is categorized as very healthy. Profitability analysis shows varied results. Meanwhile, based on FVA, Bank Syariah Indonesia and Bank BTPN Syariah show positive FVA values throughout the study period, indicating good financial performance. Conversely, Bank Panin Dubai Syariah in 2021 and Bank Aladin Syariah Tbk in 2022 and 2023 exhibit negative FVA values, indicating poor financial performance.